Dementia Data for People Living in Care Homes: Cross-sectoral National Data Linkage Study of Care Home, Healthcare and Administrative Data Sources - Mavromati, Kalliopi; Drelciuc, Maria; Lynch, Ellen; Hay, Sophie A; Hanlon, Peter; Quinn, Terry J; Burton, Jennifer Kirsty (International Journal of Population Data Science, 2026)
Introduction Dementia is common among people living in care homes, but many residents lack a diagnosis. Quantifying the prevalence of dementia in care homes is therefore challenging. Using routinely collected data, from care homes, healthcare and administrative data sources offer a potential way to address this, but the utility of these data has not been evaluated in this population. Objectives To describe the dementia status of care home residents across multiple national datasets and describe the overlaps and conflicts between sources. Methods A retrospective cohort study was undertaken using national care home data from the Scottish Care Home Census. Records for individuals in the cohort were obtained from healthcare (community prescribing, general hospital and psychiatric hospital inpatient diagnoses) and administrative data (death records). These were further categorised for their dementia diagnosis information, including specific dementia subtypes. Results A cohort of 63,308 adults living in 1,231 care homes in Scotland between 01/04/2012-31/03/2016 was created. They were 66.8% female and 86.6% died by follow-up, May 2020. Care home data identified 36,275 (57.3%) with dementia. In total, 14,269 (22.5%) had a prior prescription for a dementia medication, 13,920 (22.0%) had a general hospital discharge diagnosis of dementia, 2,750 (4.3%) had a psychiatric hospital discharge diagnosis of dementia and 31,825 (50.3%) had dementia recorded on their death certificate. We found 30.2% of the cohort had no dementia data in any national data sources and 25.3% had dementia data in all three sources and 5.1% only had dementia included in death data. Conclusions This study demonstrates the feasibility and utility of linking care home, healthcare and administrative data to better understand dementia in the population living in care homes. The contributions made by different data sources are of interest to those creating population-level datasets to understand dementia epidemiology across the population for researchers, clinicians and policymakers.